2022
DOI: 10.1007/s40820-022-00962-x
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Deficient Zn-N6 Configuration Enabling Polymeric Carbon Nitride for Visible-Light Photocatalytic Overall Water Splitting

Abstract: Despite of suitable band structures for harvesting solar light and driving water redox reactions, polymeric carbon nitride (PCN) has suffered from poor charge transfer ability and sluggish surface reaction kinetics, which limit its photocatalytic activity for water splitting. Herein, atomically dispersed Zn-coordinated three-dimensional (3D) sponge-like PCN (Zn-PCN) is synthesized through a novel intermediate coordination strategy. Advanced characterizations and theoretical calculations well evidence that Zn s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…40 Furthermore, this charge density redistribution would enable the separation of redox reactive sites, promoting charge carrier separation and suppressing back reactions, which is believed to benefit the photocatalytic activity. 41 Above theoretical calculation results suggest that the introduced electron-rich pyrimidine rings could promote exciton dissociation and charge separation by inducing the charge density redistribution in CCN-Pr x . To strengthen this deduction, XANES spectra were further recorded in dark and under illumination at C K-edge and N K-edge to monitor the photoexcited electronic transitions (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…40 Furthermore, this charge density redistribution would enable the separation of redox reactive sites, promoting charge carrier separation and suppressing back reactions, which is believed to benefit the photocatalytic activity. 41 Above theoretical calculation results suggest that the introduced electron-rich pyrimidine rings could promote exciton dissociation and charge separation by inducing the charge density redistribution in CCN-Pr x . To strengthen this deduction, XANES spectra were further recorded in dark and under illumination at C K-edge and N K-edge to monitor the photoexcited electronic transitions (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Similar to homogeneous catalysis, SACs present a well‐defined atomic structure and an adjustable coordination environment 1,2 . In recent years, SACs have become one of the best candidates for distributed energy (such as solar energy, wind energy, and tidal energy) conversion and storage due to the sufficient active sites and ultrahigh reaction selectivity 3–8 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to prepare SACs with stable structures in high metal loading is still a huge challenge 9,10 . Moreover, in consideration of the industrial applications, it is necessary for SACs to be prepared on a large scale 6 . In this review, some recently reported literatures are introduced for obtaining SACs in high metal loading or on a large scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The photocatalytic water splitting reaction needs to meet both thermodynamic and kinetic requirements. 6 Photocatalytic hydrogen production is an uphill reaction in terms of thermodynamics, requiring 237.2 kJ energy per mole of water to decompose under standard conditions. 7,8 With respect to kinetics, the conduction band of photocatalysts demands an electrochemical potential spanning the water reduction potential.…”
Section: Introductionmentioning
confidence: 99%